2021
DOI: 10.3390/foods10020345
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sensory Appeal, Nutritional Quality, Safety, and Health Determinants on Convenience Food Choice in an Academic Environment

Abstract: The present research aims to investigate the extent to which sensory appeal, nutritional quality, safety, and health determinants influence purchase intention, consumption, and satisfaction of consumers towards convenience food. The non-probability purposive sampling approach was adopted for the recruitment of consumers. A pre-tested questionnaire was used to collect data from 501 consumers. Descriptive statistics, confirmatory factor analysis, and structural equation modeling were adopted to analyze the data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 65 publications
1
40
0
3
Order By: Relevance
“…A review by Wadhera and Capaldi‐Phillips (2014) revealed that the food preferences of children are also influenced by color. Visual examination is used extensively by consumers during food selection (Imtiyaz et al., 2021; Spence, 2015). Consumers try to assess whether the food looks appetizing or not just based on appearance before actual consumption.…”
Section: Resultsmentioning
confidence: 99%
“…A review by Wadhera and Capaldi‐Phillips (2014) revealed that the food preferences of children are also influenced by color. Visual examination is used extensively by consumers during food selection (Imtiyaz et al., 2021; Spence, 2015). Consumers try to assess whether the food looks appetizing or not just based on appearance before actual consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings showed that consumer acceptability of the fruiting bodies was largely influenced by their sensory characteristics, as well as by their visual appearance. It is well-documented that sensory characteristics such as taste, appearance, freshness, texture, color, and smell are essential motivating factors to lead consumers towards the consumption of food products [ 69 ]. Overall, one of the unconventional tools for sensory evaluation of mushrooms is the smell, which is important for both the identification of species and for the oro-sensory sensations one experiences while eating them, among several issues regarding gustation and olfaction [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dry-fermented sausages are well-appreciated food specialties linked in many cases to cultural heritage, which many consumers are determined to not give up eating. Aroma, flavor, taste and texture are among the main sensory characteristics that drive consumers towards purchasing and consuming convenience food products [ 1 ]. However, it has been documented that meat product consumption is related to the prevalence of a wide range of emerging diseases such as obesity, cancer, heart-related diseases and other disorders [ 2 ].…”
Section: Introductionmentioning
confidence: 99%